Prevenção do uso de drogas e violência na escola: uma análise do projeto caravana da cidadania da secretaria de estado de segurança pública do estado do amazonas – SSP/AM em escolas públicas da zona sul da cidade de Manaus - Batista, Henrique Brasil Couto (2015)
The general objective of this thesis was to evaluate the extent to which performance of the SSP-AM through the "Citizenship Caravan Project in Schools and Communities - CEC" in the schools has contributed to decrease the trafficking and consumption of drugs as well as cases of violence in school communities serviced units. To this end, the following specific objectives were traced: the present state of the drug problem coping programs and school violence of the State Secretariat of Public Security, in particular Citizenship Caravan Project in Schools and Communities - CEC; display the number of schools and students served by the Caravan of Citizenship in Schools and Communities Project - CEC in 2013 during the implementation of the first stage of the project carried out in the south of Manaus, compiled on Citizenship of the Caravan Project Report in Schools and Communities prepared by SSP/ AM; demonstrate the importance of state action to combat and prevent drug use and violence in schools and its effects on society, highlighting the effectiveness of social programs taken over by Citizenship Caravan Project and the arrests made, seized weapons, seized money as well as types and total drugs seized; and identify from a multidimensional view of the different perceptions of the actors: managers, students, parents and community representatives from schools that were favored by the "Citizenship Caravan Project", the project's importance in combating and preventing drug use and violence in schools. As for the methodology, the work is characterized as a documentary research field. The main document used was the Citizenship Caravan Project Report in Schools and Communities - CEC prepared by SSP/ AM in 2014 drawn from 35 security commissions data formed of the following members: students, parents, teachers and public school administrators state and city located in the southern city of Manaus and participating in the project. In the search field held attended 32 schools, representing 91.4% of the total universe, representing reliably the characteristics of the survey universe, approaching the most of the researched reality (100%), meeting the level requirements established trust, maximum allowable error and percentage with which the phenomenon occurs and is distributed as follows: 32 managers; 27 students; 31 parents and 32 community representatives. To complement the survey also was held an interview with the manager of Citizenship Caravan Project. In conclusion it can be noted that the performance of the SSP-AM through preventive project "Citizenship Caravan", helped reduce the incidence of trafficking and consumption of drugs and violence in serviceable school community (students, parents and the community) and also contributed to actions as carried out arrests, seized weapons, seized money and full of seized drugs.